Roles of Gastric Emptying and Gastrointestinal Transit Following Ileal Interposition in Alleviating Diabetes in Goto-Kakizaki Rats - Wang, Yanmin; Guo, Xiaomei; Sun, Dong; Kassab, Ghassan S. (Frontiers in Endocrinology, 2022)
Objective: To determine the change of gastrointestinal (GI) emptying time after ileal interposition (IT), and elucidate the role of altered GI peristalsis in diabetic control. Materials and methods: Twelve male Goto-Kakizaki rats were randomly divided into IT and sham groups. Body weight and food intake were recorded. Oral glucose tolerance test (OGTT), insulin tolerance test (ITT), plasma glucagon-like peptide-1 (GLP-1) and gastric emptying were measured at baseline and 4 and 8 weeks after operation. At 9 weeks postoperatively, the rats in IT group were given atropine which can suppress the emptying of stomach and upper intestine, while sham rats were given metoclopramide (to expedite gastric emptying) for 1 week. At week 10 postoperatively, OGTT and GLP-1 were detected. The intestinal transit was tested at postoperative 12 weeks. Results: No differences were found between groups at baseline. After operation, the IT rats had lower body weight than sham rats. At 4 and 8 weeks postoperatively, the IT group showed better OGTT and ITT, with significantly elevated GLP-1 relative to sham. After administration of the GI motility drugs, however, the effect of diabetic control for the two groups became similar. The GI transit after IT was significantly slower than sham at all tested time points. Conclusions: Although IT inhibits the GI transit time, the earlier interaction between undigested nutrients and interpositioned ileum promotes gut hormone secretion and thus reduces body weight and alleviates hyperglycemia. A decrease of GI transit of IT rats exacerbates the anti-diabetic effects.